Gynura tambuyukonensis (Asteraceae), an obligate ultramafic species endemic to Mount Tambuyukon (Kinabalu Park, Sabah, Malaysia) - van Der Ent, Antony; Vanijajiva, Ongkarn (Phytotaxa, 2014)
A new endemic species of Gynura is described and illustrated. Gynura tambuyukonensis is found exclusively (‘obligate’) on ultramafic soils between bare peridotite bedrock at 2450–2550 m above sea level on Mount Tambuyukon (Kinabalu Park) in Sabah (Malaysia) on Borneo Island. On the basis of the morphological features, this new taxon appears to be related to G. sundaiaca F.G. Davies of the Lesser Sunda Islands and Timor. The diagnostic morphological characters are discussed and information about its habitat, ecology and distribution is provided.